2002
DOI: 10.1038/sj.mp.4001143
|View full text |Cite
|
Sign up to set email alerts
|

Chromaffin cell function and structure is impaired in corticotropin-releasing hormone receptor type 1-null mice

Abstract: Corticotropin-releasing hormone (CRH) is both a main regulator of the hypothalamic-pituitaryadrenocortical axis and the autonomic nervous system. CRH receptor type 1 (CRHR1)-deficient mice demonstrate alterations in behavior, impaired stress responses with adrenocortical insufficiency and aberrant neuroendocrine development, but the adrenal medulla has not been analyzed in these animals. Therefore we studied the production of adrenal catecholamines, expression of the enzyme responsible for catecholamine biosyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 59 publications
(62 reference statements)
1
20
0
Order By: Relevance
“…In the CRH-R1 receptor-deficient mice an impairment of both, adrenocortical and adrenomedullary function was found. Epinephrine release and the PNMT gene expression were significantly reduced in AM of these animals (Yoshida-Hiroi et al, 2002). Similarly, we found an impairment of the PNMT mRNA levels and epinephrine release in CRH knockout mice under stress conditions.…”
Section: Discussionmentioning
confidence: 70%
“…In the CRH-R1 receptor-deficient mice an impairment of both, adrenocortical and adrenomedullary function was found. Epinephrine release and the PNMT gene expression were significantly reduced in AM of these animals (Yoshida-Hiroi et al, 2002). Similarly, we found an impairment of the PNMT mRNA levels and epinephrine release in CRH knockout mice under stress conditions.…”
Section: Discussionmentioning
confidence: 70%
“…For example, ACTH, the principal positive regulator of adrenal steroidogenesis, induces an increase in mitochondrial abundance in adult human adrenocortical cells (18). In contrast, mice lacking CRH receptor-1 display a decrease in the amount of mitochondria in adrenocortical cells, consistent with decreased corticosterone production in these animals (19). Thus, the inhibition of 8-Br-cAMP-stimulated progesterone production in Y-1 cells transfected with OSAP siRNA may be secondary to the reduced cellular mitochondrial content, suggesting a role for OSAP in maintaining mitochondrial abundance.…”
Section: Discussionmentioning
confidence: 80%
“…The function of the adrenal medulla of Crf 1 -/-and Crf -/-mice is similarly impaired. Thus, basal epinephrine levels in Crf 1 -/-mice are less than 50% those of WT littermates, and PNMT mRNA levels in Crf 1 -/-mice are only 25% the level of their WT controls [170]. Histological examination revealed that chromaffin cells in Crf 1 -/-mice exhibit marked depletion in epinephrine-storing secretory granules, which was not completely normalized by ACTH treatment, suggesting that CRF 1 is required for normal chromaffin cell structure and function and that deletion of this gene is associated with a significant impairment of epinephrine biosynthesis.…”
Section: Adrenal Crf and Ucns And Their Receptors: Lessons From Knockmentioning
confidence: 88%